Are Counterparty Arrangements in Reinsurance a Threat to Financial Stability? - Davison, Matt; Leadbetter, Darrell; Lu, Bin; Voll, Jane (Assurances et gestion des risques / Insurance and Risk Management)

(untitled) (Faculté des sciences de l'administration, Université Laval, 2019)
Interconnectedness among insurers and reinsurers at a global level is not well understood and may pose a significant risk to the sector, with implications for the macroeconomy. Models of the complex interactions among reinsurers and with other participants in the financial system and the real economy are at a very early stage of development. Parts of the market remain opaque to both regulators and market participants, particularly the counterparty arrangements among reinsurers through retrocession agreements. The authors create several plausible networks to model these relationships, each consistent with the financial statement data of the reinsurer. These networks are stress-tested under a series of severe but plausible catastrophic-loss scenarios. This analysis contributes to the literature by (i) applying a network-model approach common in the banking literature to the insurance industry; (ii) assessing the interconnections among reinsurers through potential claims rather than premiums; and (iii) investigating the most opaque part of the global insurance market, namely, counterparty arrangements among global reinsurers (retrocession). The authors find that contagion in the global reinsurance market is plausible and that the size of the potential market disruption is sensitive to (i) the distribution of risk among counterparties, (ii) the trigger for financial distress, (iii) the time horizon for claims resolution and (iv) the degree of loss netting. The findings suggest that further study of industry practices in these four areas would improve our ability to assess risk in the insurance sector and promote financial stability.